Capitals and networks : a sociology of Paris' black churches - (:unkn) unknown (My University, 2010)
This paper is the first quantitative analysis of the social world composed by African immigrants' churches in and around Paris, France. The data are based on an unusual material: advertisement posters for religious events. With these data I can conceive of this world as structured by an unequal allocation of capitals and by the establishment of cross-relationships among actors. Protestant black churches, since the end of the 1990s, have publicly advertised their main religious events. The posters publicize a number of specific elements (location, description of the religious product, hierarchic titles...). With more than one hundred posters (gathered since july, 2008), my paper proposes both a quantitative sociography of this world, and an attempt to theorize its inner working. After analysis, thoses churches appear to be transnational churches located in poor neighborhoods in the northern suburbs of Paris, they are churches of " pastors " rather than " prophets " (one third of the titles worn by the characters is " pastor "), churches that propose "seminars", "conventions" or "day" more than half the time (and rarely "crusades"). Those churches combine in the same move an intense competition and collaborative networking. I use in this paper the invitations and counter-invitations advertized on the posters to draw and analyse part of this collaborative network. It is not a dense network, but it seems to follow some basic rules.
Keywords: African Research